Microwave Assisted Synthesis of ZnO Tridimensional Nanostructures. (2015) - Barreto, G.; Morales, G.; Cañizo, A.; Eyler, N.
Abstract: The effect of different variables (reactive precursors, additives, stoichiometric ratio) on the final morphology of nano-ZnO obtained by a microwave-assisted technique has been investigated. The characterization of the samples was carried out by scanning electron microscopy in transmission mode (FE-SEM), infrared spectroscopy (FTIR) and x-ray diffraction (XRD). The results showed that all the above-mentioned variables influenced to some extent, the shape and/or size of the synthesized nanoparticles. In particular, the addition of an anionic surfactant (sodium di-2-ethylhexyl sulfosuccinate, AOT) to the reaction mixture allowed the synthesis of complex tridimensional particles with uniform size distributions and morphology.